Characteristics and formation mechanisms of tight oil: A case study of the Huahai Depression, Jiuquan Basin, Northwest China. Issue 1 (January 2019) - Fan, Chunyan; Tang, Xianglu; Zhang, Yuanyin; Song, Yan; Jiang, Zhenxue; Luo, Qun; Li, Baiying
The exploration of tight oil reservoirs has achieved a big success, especially in the Huahai Depression, Jiuquan Basin, China, but the characteristics and formation mechanisms of the tight oil reservoir are unclear. In this paper, a series of analyses including thin section, scanning electron microscope, gas chromatography–mass spectrometry, isotope, and fluid inclusions were taken to study the tight reservoirs of the Xiagou Formation (K1 g) and Zhonggou Formation (K1 z) in the Huahai Depression. The results show that the main factors influencing the porosity and permeability of the tight reservoir are the compaction and two periods of carbonate cementation. The second type of carbonate cementation was related to the decarboxylation of organic acids in parts of the study area. The tight oil accumulation periods for different formations are confirmed, during 115–102 Ma in K1 g1, 114–97 Ma in K1 g2, and 103–85 Ma in K1 z1, respectively. The tight oil migrations are executed for only several meters vertically but hundreds of meters even kilometers laterally. Two kinds of formation mechanisms exist in the study area. The main formation pattern is the "hydrocarbon accumulated after reservoir had tightened, " which has occurred in most of the study area. The other pattern, the "hydrocarbon accumulated during reservoir was tightening, " is found in several places of the study area.